SOIL CORROSIVITY DETERMINATION FOR THE ENGINEERING DESIGN OF BURRIED PIPES USING GEOPHYSICAL INVESTIGATION ALONG JOS – BUKURU METROPOLIS - ABALAKA, I.E; OLUWAFEMI, ILESANMI (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
The study area is around Jos – Bukuru metropolis. Areas 1, 2, 3, 4, 6, 7, 8, 11, 13, 14, 16 and the Main Line were investigated where their resistivity’s in Ωm ( Ohm – metres) were determined. The geophysical investigation method used for this investigation was the electrical resistivity method employing the Schlumberger technique with current electrode spreading from 1.5 to 18m with the depth penetration capacity of 6m. The spread was so chosen because the investigation seek to determine the soil corrosivity from the surface to a depth of 5m underground. Resistivity results revealed that Areas 1, 8, 11 and 16 are mildly corrosive with resistivity range of 126.20 – 193.51 Ωm while Areas 2, 3, 4, 6, 7, 13, 14 and the Main Line were essentially non corrosive with resistivity range of 211.24 – 515.56 Ωm. From the geophysical investigation carried out and the results obtained from data analysis and interpretations, the area under investigation is mostly non-corrosive. However, the average resistivities of some VES points shows that the soil in those points are highly corrosive to moderately corrosive. The average resistivity of the entire project area infers that the soils in the area is essentially non corrosive and the metallic pipes can be conveniently laid since close to 70 % of the area under investigation are non corrosive.